Polybenzoxazole symmetric film, superfine polybenzoxazole hollow fiber asymmetric film, and preparation methods and applications of polybenzoxazole symmetric film and superfine polybenzoxazole hollow fiber asymmetric film
By introducing anchor twisted dianhydride groups into the polymer film, the rigidity of the polyimide molecular chain is improved, and a uniform pore structure is formed through thermal rearrangement, the low separation caused by uneven cavity in the polymer film is solved. Performance issues, achieving higher gas separation performance and better mechanical properties.
Patent Information
- Application Number
- CN202411483948.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-18
AI Technical Summary
The cavity sizes in existing polymer films are uneven and widely distributed, resulting in low separation performance and gas separation performance is limited by the balance between gas permeability and selectivity.
By anchoring the twisted dianhydride group, the movement of the group is restricted, the molecular chain of the polyimide precursor increases rigidity, and a more uniform and controllable pore structure is formed during the thermal rearrangement process, thereby improving the symmetry of polybenzoxazole Gas separation properties of films.
The gas separation performance of polybenzoxazole symmetric films has been improved, including improving permeability and selectivity, and enhancing anti-plasticization and anti-aging capabilities.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polybenzoxazole symmetrical film, an ultrafine polybenzoxazole hollow fiber asymmetric membrane, and a preparation method and application thereof. Background Art
[0002] Energy shortage and environmental pollution are important issues concerning human survival and development. To promote green and low-carbon development, on the one hand, we need to develop clean energy and energy storage technology, and on the other hand, we need to reduce carbon dioxide emissions and capture and recycle the CO2 that has already been emitted. Whether it is the mining of clean energy or the capture and recycling of gas, gas separation technology plays an important role.
[0003] As a new gas separation technology, membrane separation technology has obvious advantages over traditional methods such as low-temperature distillation. The membrane separation process does not undergo phase change, does not require the addition of separation agents, is energy-efficient and low-cost, so membrane separation technology is recognized as the gas separation technology with the greatest development potential in the 21st century.
[0004] Among the many membrane materials, polymers dominate large-scale applications due to their versatility, ease of processing, and good mechanical properties. However, the cavities in polymer membranes are uneven in size and widely distributed, resulting in low separation performance, and gas separation performance is limited by the balance between gas permeability and selectivity (Robertson upper limit).
[0005] Polybenzoxazole (PBO) is a new type of polymer with high free volume elements and narrow cavity size distribution based on rigid and microporous structure. It has high permeability, good selectivity, excellent anti-plasticization performance and great development potential. The performance of PBO is related to many factors in its formation process, such as precursor structure, synthesis path, reaction time, temperature, and conversion rate of polyimide to PBO.
[0006] Among them, the effects of precursor structure are more studied, such as ortho-hydroxy polyimide (HPIs-TMBDA) containing a rigid diphenyl center and four methyl groups; introducing three (polyhydroxyimide) precursors; mixing orthogonal functionalized polyimide (API) and polyamide (PHA) precursor materials; combining co-diamines (mPDA, DMB and TFMB) with different substitution groups to ortho-hydroxy polyimide (HPI) precursors; in-situ heat treatment of poly-o-hydroxyamide-cobaltamide (PHAA) precursors; acetylation of polyhydroxyimine with acetic anhydride to change the ortho functional groups on the polymer chain, etc. However, most of the above studies are about the structural regulation of diamines and the introduction of rigid groups to improve the comprehensive properties of polybenzoxazoles. Summary of the invention
[0007] The present invention provides a polybenzoxazole symmetrical film, an ultrafine polybenzoxazole hollow fiber asymmetric membrane, and a preparation method and application thereof, which anchors twisted dianhydride groups and restricts the movement of the groups, thereby increasing the rigidity of the polyimide precursor molecular chain, and forming a more uniform and controllable pore structure of PBO during the thermal rearrangement process, thereby achieving the improvement of the gas separation performance of the polybenzoxazole symmetrical film.
[0008] The present invention provides a polybenzoxazole symmetrical film, wherein the polybenzoxazole has a structure as shown in formula (I): Formula (I); Among them, 10 <n<500; X is independently selected from: , , , , , or ; Ar is independently selected from: , , , , , or .
[0009] The present invention also provides a method for preparing a polybenzoxazole symmetrical film, comprising the following steps: S1. Under a protective atmosphere, a ladder-shaped dianhydride and an o-hydroxy diamine are mixed, a catalyst and a solvent are added, and the temperature is raised to 150-180° C. to react to obtain a viscous reaction solution; S2, treating the viscous reaction solution by solvent precipitation method, drying, and obtaining polyimide; S3, dissolving the polyimide in a solvent, placing the resulting solution in a culture dish, and evaporating the solvent to obtain a polyimide film; S4, placing the polyimide film in a tube furnace, and heat treating it at 350-500° C. for 0.5-2 h to obtain a polybenzoxazole symmetrical film; Wherein, in step S1, the ladder-structured dianhydride is selected from the following: ; wherein X is independently selected from: , , , , , or .
[0010] Further, in step S1, the o-hydroxy diamine is selected from the following: , , , , , or .
[0011] Furthermore, in step S1, the ratio of the ladder-structured dianhydride, o-hydroxydiamine, and catalyst is 2 mmol:2 mmol:0.3~2 mL.
[0012] Further, in step S1, the catalyst is selected from a basic catalyst or an acidic catalyst; Preferably, the alkaline catalyst comprises at least one of isoquinoline and triethylamine; Preferably, the acidic catalyst includes at least one of benzoic acid and p-hydroxybenzoic acid. Furthermore, in step S2, the viscous reaction liquid is treated by a solvent precipitation method, which specifically includes: pouring the viscous reaction liquid into a mixed solution of ethanol and water, stirring to precipitate polyimide, and filtering; wherein the volume ratio of ethanol to water in the mixed solution of ethanol and water is 1:1; In step S2, the drying is specifically performed at 80-120° C. for 10-20 h.
[0013] Further, in step S1, the solvent includes at least one of m-cresol, N-methylpyrrolidone, N, N-dimethylformamide, N, N-dimethylacetamide, and dimethyl sulfoxide; In step S3, the solvent is a volatile solvent; preferably, the volatile solvent includes at least one of tetrahydrofuran, 1,4-dioxane, chloroform and dichloromethane.
[0014] The present invention also provides an ultrafine polybenzoxazole hollow fiber asymmetric membrane, wherein the polybenzoxazole has a structure as shown in formula (I): Formula (I); Among them, 10 <n<500; X is independently selected from: , , , , , or ; Ar is independently selected from: , , , , , or .
[0015] The present invention also provides a method for preparing an ultrafine polybenzoxazole hollow fiber asymmetric membrane, comprising the following steps: Y1. Dissolve polyimide in a benign solvent, add a porogen and a low boiling point solvent, and stir to obtain a casting solution; Y2, placing the casting solution obtained in step Y1 into a material tank for degassing, and obtaining an ultrafine hollow fiber gas separation membrane by dry-jet wet spinning; Y3, placing the ultrafine hollow fiber gas separation membrane obtained in step Y2 in a tubular furnace at 350-500° C. for heat treatment for 0.5-2 h to obtain an ultrafine PBO hollow fiber gas separation membrane; Wherein, in step Y1, the polyimide is obtained through steps S1-S2 in the method for preparing polybenzoxazole according to claim 3. The present invention also proposes the use of the above-mentioned polybenzoxazole symmetrical film and the above-mentioned ultrafine polybenzoxazole hollow fiber asymmetric membrane in gas separation, and the application includes: A polybenzoxazole symmetrical film or an ultrafine polybenzoxazole hollow fiber asymmetric membrane is used to obtain H2 from a H2 / N2 mixed gas, to enrich O2 from an O2 / N2 mixed gas or to obtain high-concentration N2 from the air, to separate CO2 from a CO2 / CH4 mixed gas, to separate H2 from a H2 / CH4 mixed gas or to separate CO2 from a CO2 / N2 mixed gas.
[0016] The present invention has the following advantages: The PBO symmetric film and preparation method thereof proposed in the present invention are obtained by thermal rearrangement of a polyimide containing an anchored twisted dianhydride group. The twisted dianhydride is anchored by linking an ether bond on a benzene ring. Due to the linking of oxygen atoms in the additional ether bond, the originally twisted group becomes difficult to move, thereby improving the rigidity of the polymer chain. In addition, the reaction rate is faster and the conversion rate is higher during thermal rearrangement. The number of micropores on the surface of the polybenzoxazole symmetric film obtained after thermal rearrangement increases, the gas permeability is higher, and thus the gas separation performance (such as permeability and selectivity) is also significantly improved.
[0017] The present invention also proposes an ultrafine PBO hollow fiber asymmetric membrane and a preparation method thereof, wherein anchored twisted dianhydride and o-hydroxy diamine are used as reaction raw materials, high-performance PI is screened out by anchoring twisted dianhydride groups, and then a casting solution containing PI is prepared, and a PBO hollow fiber asymmetric membrane is obtained by heat treatment after membrane preparation. The hollow fiber membrane obtained by the method has a large specific surface area, which increases the contact surface in the gas separation process and significantly improves the gas flux and separation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0019] Figure 1 The NMR spectra of the polyimide obtained in the examples and comparative examples of the present invention are shown in FIG. Figure 2 The infrared spectra of the polyimide and polyimide film obtained in the examples and comparative examples of the present invention are shown; Figure 3 The specific surface area test (BET) diagram of the polyimide film obtained in the examples and comparative examples of the present invention; Figure 4 The pure gas separation performance analysis diagram of the polyimide and polyimide film obtained in the examples and comparative examples of the present invention; Figure 5 The scanning electron microscope (SEM) images of the hollow fiber gas separation membranes obtained in the examples and comparative examples of the present invention are shown. DETAILED DESCRIPTION The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.
[0020] On the one hand, an embodiment of the present invention provides a polybenzoxazole (PBO) film, wherein the polybenzoxazole has a structure as shown in formula (I): Formula (I); Among them, 10 <n<500; X is independently selected from: , , , , , or ; Ar is independently selected from: , , , , , or .
[0021] It should be noted that Ar is independently selected from the structure and the dotted lines represent the bond positions.
[0022] Acid anhydrides are a class of organic compounds that are usually formed by the dehydration reaction of two carboxylic acid molecules. The dehydration reaction can be intramolecular or intermolecular. The general structure of an acid anhydride can be expressed as RC(=O)-OC(=O)-R', where R and R' are alkyl or aromatic groups. The compound structure containing two acid anhydrides in a monomer is called a dianhydride, or dianhydride for short.
[0023] The PBO film proposed in the embodiment of the present invention is obtained by thermal rearrangement of a polyimide (PI) containing an anchored twisted dianhydride group, and the polyimide is obtained by polymerization reaction of a ladder-structured dianhydride and an ortho-hydroxy diamine. The inventor of the present application first proposed to adjust the twisted dianhydride group to an anchored twisted dianhydride group (ladder-structured dianhydride). The twisted dianhydride group refers to a dianhydride with no link between symmetrical benzene rings, and the dianhydride side chain can rotate. The anchored twisted dianhydride group refers to a linking group between symmetrical benzene rings of the dianhydride, which restricts its twisting movement to a certain extent. By introducing a ladder-structured dianhydride, the twisted dianhydride is anchored by linking an ether bond on the benzene ring, and the single-bonded benzene ring is anchored by an additional ether bond. Due to the link of the oxygen atom, the twisted group becomes difficult to move, which improves the rigidity of the polymer chain and the free volume, thereby making the gas separation performance (such as selectivity and permeability) of the PBO film obtained after thermal rearrangement higher.
[0024] Preferably, X is independently selected from: .
[0025] On the other hand, an embodiment of the present invention further provides a method for preparing a PBO film, comprising the following steps: S1. Under a protective atmosphere, a ladder-shaped dianhydride and an o-hydroxy diamine are mixed, a catalyst and a solvent are added, and the temperature is raised to 150-180° C. to react to obtain a viscous reaction solution; S2, treating the viscous reaction solution by solvent precipitation method, drying, and obtaining polyimide; S3, dissolving the polyimide in a solvent, adding the resulting solution into a culture dish, and evaporating the solvent to obtain a polyimide film; S4, placing the polyimide film in a tube furnace, and heat treating it at 350-500° C. for 0.5-2 h to obtain a polybenzoxazole symmetrical film; Wherein, in step S1, the ladder-structured dianhydride is selected from the following: ; wherein X is independently selected from: , , , , , or .
[0026] The preparation method of the PBO film proposed in the present invention uses a ladder-shaped dianhydride and an ortho-hydroxy diamine as reaction raw materials, and links an ether bond on the twisted dianhydride group to form an anchored twisted dianhydride group, that is, a ladder-shaped dianhydride group that restricts movement. After the ladder-shaped dianhydride reacts with the ortho-hydroxy diamine to obtain a polyimide (PI), a PI film is formed, and then the PI film is heat-treated to obtain a PBO film. In the reaction, the ladder-shaped structure can effectively restrict the movement of the dianhydride group, so that the conversion rate of PI to PBO is faster, the rigidity of the molecular chain segment is enhanced, and the PBO structure obtained by thermal rearrangement improves the gas permeability coefficient and selectivity, and strengthens the anti-plasticization and anti-aging capabilities. This technology fills the research gap in the structure-activity relationship between the anchored twisted group and the thermally rearranged polybenzoxazole.
[0027] In one embodiment of the present invention, in step S1, the o-hydroxy diamine is selected from the following: , , , , , or .
[0028] In the embodiment of the present invention, in step S1, a viscous reaction liquid containing polyimide is obtained by reacting a ladder-structured dianhydride monomer and an ortho-hydroxy diamine monomer under the action of a catalyst.
[0029] In one embodiment of the present invention, in step S1, the amount ratio of the ladder-structured dianhydride, o-hydroxydiamine, and catalyst is 2 mmol:2 mmol:0.3~2 mL. In a preferred embodiment of the present invention, in step S1, the catalyst is selected from a basic catalyst or an acidic catalyst.
[0030] Furthermore, in step S1, the alkaline catalyst includes at least one of isoquinoline and triethylamine.
[0031] Furthermore, in step S1, the acidic catalyst includes at least one of benzoic acid and p-hydroxybenzoic acid. In the embodiment of the present invention, the catalyst is in a liquid state at room temperature and is directly added in a liquid state. The catalyst that is not in a liquid state at room temperature can be heated to a molten state before being added.
[0032] In one embodiment of the present invention, in step S1, the solvent includes at least one of m-cresol, N-methylpyrrolidone, N, N-dimethylformamide, N, N-dimethylacetamide, and dimethyl sulfoxide. In this embodiment of the present invention, the volatilization process is used to remove the organic solvent and precipitate the polymer by phase inversion.
[0033] In one embodiment of the present invention, in step S1, the usage ratio of o-hydroxydiamine to solvent is 2 mmol:5-30 mL.
[0034] In one embodiment of the present invention, in step S1, the protective atmosphere includes at least one of nitrogen and argon.
[0035] In a preferred embodiment of the present invention, in step S1, the reaction time is 1-5 h.
[0036] In one embodiment of the present invention, in step S1, the viscosity of the obtained reaction solution is 6000-20w cps.
[0037] In the embodiment of the present invention, in step S2, a solvent precipitation method is used to precipitate the polyimide polymer in the obtained viscous reaction solution. In a preferred embodiment of the present invention, in step S2, the viscous reaction liquid is treated by a solvent precipitation method, specifically comprising: pouring the viscous reaction liquid into a mixed solution of ethanol and water, stirring to precipitate polyimide, and filtering; wherein the volume ratio of ethanol to water in the mixed solution of ethanol and water is 1:1. The above operation can be repeated 1-5 times.
[0038] In a preferred embodiment of the present invention, in step S2, the drying is specifically drying at 80-120° C. for 10-20 h.
[0039] In a preferred embodiment of the present invention, in step S2, the drying is performed in a vacuum oven.
[0040] In the embodiment of the present invention, in step S3, a solvent volatilization method is used to prepare a polyimide film from a polyimide polymer.
[0041] In one embodiment of the present invention, in step S3, the solvent is a volatile solvent. Preferably, the volatile solvent includes at least one of tetrahydrofuran, 1,4-dioxane, chloroform and dichloromethane.
[0042] In one embodiment of the present invention, step S3 further comprises drying the obtained polyimide film in a vacuum oven at 80-120°C for 10-14 h, and further heating it in a tube furnace under a protective atmosphere at 200-250°C for 1-3 h to ensure that the remaining solvent is completely removed. Preferably, the obtained polyimide film is dried in a vacuum oven at 100°C for 12 h, and further heated in a tube furnace under a protective atmosphere at 230°C for 2 h to ensure that the residual solvent is completely removed.
[0043] In the embodiment of the present invention, in step S4, the polyimide film is subjected to a thermal rearrangement reaction to obtain a PBO film. The reaction equation of the PBO film is as follows: .
[0044] In the embodiment of the present invention, the thermal rearrangement is to heat-treat the polyimide formed by the polymerization of the ladder-shaped dianhydride and the ortho-hydroxy diamine, and thermal rearrange to form a PBO structure. During the thermal treatment, the conversion of the polyimide linked by oxygen atoms to polybenzoxazole (i.e., thermal rearrangement) is faster and has a higher conversion rate. After the thermal treatment, the PBO membrane based on the ladder-shaped dianhydride structure has more micropores on the surface, a higher gas permeability, and an improved selectivity.
[0045] Furthermore, step S4 also includes, before the heat treatment, performing thermogravimetric analysis on the polyimide film to determine the optimal heat treatment temperature and heat treatment time of the obtained polyimide film. In the embodiment of the present invention, due to the different molecular structures of different polyimides, the temperature and time required for thermal rearrangement are also different, and the optimal temperature and time of thermal rearrangement reaction can be determined by thermogravimetric analysis. Furthermore, the thermogravimetric analysis is specifically to place the polyimide in a crucible, and analyze the thermal weight loss of the polyimide by a thermogravimetric analyzer in a nitrogen atmosphere at a heating rate of 5°C / min from 30°C to 800°C, to determine the temperature at which thermal rearrangement occurs and the time required for thermal rearrangement to occur.
[0046] Preferably, the temperature of the heat treatment is 350-500 ° C, and the time of the heat treatment is 0.5-2 h. The temperature and time of the optimal heat treatment are both within this range. The determination of the optimal heat treatment temperature is based on the thermal weight loss of the material. Generally, the thermal rearrangement process occurs between 350-500 ° C. In this temperature range, the hydroxyl and carbonyl groups in the polymer will undergo a re-cyclization process and release H2O and CO2, resulting in thermal weight loss of thermal rearrangement. Therefore, the specific temperature and time of the heat treatment can be determined based on the thermal weight loss process of the specific material.
[0047] In one embodiment of the present invention, the thickness of the obtained polybenzoxazole symmetrical film is 50-80 μm.
[0048] On the other hand, the embodiment of the present invention also proposes the application of the polybenzoxazole (PBO) film in gas separation. In the embodiment of the present invention, by regulating the movement of the twisted dianhydride groups, the controllability of the polybenzoxazole conversion rate is effectively improved, so that the conversion rate is greatly improved and the gas separation performance is optimized. Furthermore, the application includes: using PBO film to obtain H2 from H2 / N2 mixed gas, enrich O2 from O2 / N2 mixed gas or obtain high-concentration N2 from air, separate CO2 from CO2 / CH4 mixed gas, separate H2 from H2 / CH4 mixed gas or separate CO2 from CO2 / N2 mixed gas.
[0049] In another aspect, an embodiment of the present invention further provides an ultrafine polybenzoxazole hollow fiber asymmetric membrane, wherein the polybenzoxazole has a structure as shown in formula (I): Formula (I); Among them, 10 <n<500; X is independently selected from: , , , , , or ; Ar is independently selected from: , , , , , or .
[0050] In the embodiments of the present invention, the PBO film and the PBO hollow fiber gas separation membrane are both common membranes in the membrane separation field, wherein the PBO film is a symmetric membrane and the PBO hollow fiber gas separation membrane is an asymmetric membrane. The two have different physical forms, evaluation indicators, and application fields, and therefore have different preparation methods.
[0051] In another aspect, an embodiment of the present invention further provides a method for preparing an ultrafine polybenzoxazole (PBO) hollow fiber asymmetric membrane, comprising the following steps: Y1. Dissolve polyimide in a benign solvent, add a porogen and a low boiling point solvent to obtain a casting solution; Y2, placing the casting solution obtained in step Y1 into a material tank for degassing, and obtaining an ultrafine hollow fiber gas separation membrane by dry-jet wet spinning; Y3, placing the ultrafine hollow fiber gas separation membrane obtained in step Y2 in a tubular furnace at 350-500°C for heat treatment for 0.5-2 h to obtain an ultrafine PBO hollow fiber asymmetric membrane; The polyimide in step Y1 is obtained through steps S1-S2 in the above-mentioned polybenzoxazole preparation method.
[0052] The ultrafine PBO hollow fiber asymmetric membrane proposed in the embodiment of the present invention uses anchored twisted dianhydride and o-hydroxy diamine as reaction raw materials, screens out high-performance PI by anchoring twisted dianhydride groups, and then prepares a casting solution containing PI, and heat treats the membrane after film formation to obtain a PBO hollow fiber asymmetric membrane. The hollow fiber membrane obtained by this method has a large specific surface area, which increases the contact surface in the gas separation process and significantly improves the gas flux and separation performance.
[0053] In one embodiment of the present invention, in step Y1, the mass ratio of polyimide, benign solvent, porogen and low boiling point solvent is 10-35%: 20-70%: 1-10%: 10-30%. The solid content of the obtained casting solution is 10-35%wt.
[0054] In one embodiment of the present invention, in step Y1, the porogen includes at least one of polyvinyl pyrrolidone (PVP) or polyethylene glycol, and the low boiling point solvent includes at least one of tetrahydrofuran, ethanol or tert-butyl alcohol.
[0055] In one embodiment of the present invention, in step Y1, the benign solvent is screened by the following method: according to the polyimide obtained in step S2, the solubility parameter of the polymer is calculated by the group contribution method, and the corresponding benign solvent is selected. The group contribution method is a conventional method in the art, and the following literature can be referred to for details: GOYDAN R, REID RC, TSENG H S. Estimation of the solubilities of organic compounds in polymers by group-contribution methods [J]. Industrial & Engineering Chemistry Research, 1989, 28 (4): 445-454. Preferably, the benign solvent may be at least one of N-methylpyrrolidone (NMP), N, N-dimethylacetamide (DMAc), N, N-dimethylformamide (DMF), dichloroethane or dimethyl sulfoxide (DMSO).
[0056] In one embodiment of the present invention, in step Y2, the degassing treatment time is 12-36 hours. Preferably, the degassing treatment time is 24 hours. In an embodiment of the present invention, in step Y2, the dry-jet wet spinning method is a method well known to those skilled in the art, specifically: the casting liquid is squeezed out from the spinneret by pressurization. Since the coagulation bath is a non-solvent for the polymer, solvent exchange occurs when the casting liquid enters the coagulation bath. The entry of the non-solvent coagulation bath causes the polymer to precipitate and a phase inversion occurs. The core liquid helps it form a hollow structure inside, and a hollow fiber membrane is obtained by stretching with a roller.
[0057] Furthermore, in step Y2, the core liquid is a mixed solution of N-methyl-2-pyrrolidone (NMP): water = 90:10, and the flow rate ratio of the core liquid to the casting liquid is 1:3.
[0058] In one embodiment of the present invention, in step Y3, the outer diameter of the obtained ultrafine PBO hollow fiber gas separation membrane is 300-500 μm.
[0059] On the other hand, the embodiments of the present invention further provide the application of ultrafine PBO hollow fiber gas separation membrane in gas separation. In one embodiment of the present invention, the application includes: using an ultrafine PBO hollow fiber gas separation membrane to obtain H2 from a H2 / N2 mixed gas, enriching O2 from an O2 / N2 mixed gas or obtaining high-concentration N2 from the air, separating CO2 from a CO2 / CH4 mixed gas, separating H2 from a H2 / CH4 mixed gas or separating at least one of CO2 from a CO2 / N2 mixed gas.
[0060] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings.
[0061] Example 1-1 A method for preparing a symmetrical film of polybenzoxazole (PBO) based on a ladder-structured dianhydride comprises the following steps: The reaction formula of PBO film (6FCDA-HAB-TR) is as follows: (1) Under argon protection, 9, 9-bis(trifluoromethyl)-2, 3, 6, 7-oxanthene tetracarboxylic dianhydride (denoted as: 6FCDA) (0.9164 g, 2 mmol), 3, 3'-dihydroxybenzidine (denoted as HAB) (0.4324 g, 2 mmol) and solvent m-cresol (6 mL) were added to a 25 mL polymerization tube in sequence, 1 mL of catalyst isoquinoline was added dropwise, a magnetic bar was added for stirring, and the mixture was heated to 160 °C for reaction for 3 h. The product was brown and viscous with a viscosity of about 10w cps. The obtained viscous solution was slowly poured into a stirred ethanol / water = 1:1 mixed solution (1000 mL). The polymer solution precipitated in a fibrous state, stirred, and then filtered to obtain the product. The mixed solvent of ethanol and water was replaced 5 times to completely remove the unreacted m-cresol, and finally dried in a vacuum oven at 120 ° C for 15 h until constant weight was obtained to obtain a polymer, polyimide GCPI, also recorded as 6FCDA-HAB; (2) The obtained polyimide was dissolved in tetrahydrofuran to prepare a solution with a solid content of 2%wt. The insoluble matter and impurities were removed by a filter, and the filtered solution was poured into a petri dish with a diameter of 6 cm. The solvent was evaporated and the polymer phase was transformed into a membrane. After the solvent was evaporated, it was dried in a vacuum oven at 100 °C for 12 h, and further heated in a tube furnace at 230 °C for 2 h under N2 atmosphere to ensure that the remaining solvent was completely removed, and a polyimide film was obtained, which was also recorded as 6FCDA-HAB film; (3) The 6FCDA-HAB film was subjected to thermal rearrangement treatment, specifically: polyimide was placed in a crucible, and the thermal weight loss of polyimide was analyzed by a thermogravimetric analyzer in a nitrogen atmosphere at a heating rate of 5 °C / min from 30 °C to 800 °C. Through thermogravimetric analysis, it began to rearrange at 400 °C, and the thermal rearrangement reaction rate reached the maximum at 440 °C. The temperature at which the thermal rearrangement occurred was finally determined to be 440 °C, and the time required for the thermal rearrangement to occur was 2 h. After the thermal rearrangement treatment, the polybenzoxazole symmetric film GCPO was obtained after natural cooling to room temperature, which was recorded as 6FCDA-HAB-TR film with a thickness of 50 µm.
[0062] Structural characterization: 6FCDA-HAB: 1 H NMR (400 MHz, DMSO-d6) δ 9.65 (s, 2H, -OH), 8.29 (s,2H), 8.08 (s, 2H), 7.20 (s, 3H), 6.48 (s, 3H). The peaks in the H NMR spectrum of the obtained 6FCDA-HAB(GCPI) are as follows: Figure 1 shown.
[0063] The infrared spectra of the obtained 6FCDA-HAB (GCPI) and 6FCDA-HAB-TR (GCPO) films showed the following peaks at 1780, 1720, and 1380 cm - The absorption peak of the imide ring is shown at ¹ Figure 2 shown.
[0064] Gas separation performance test: The pure gas permeation performance of 6FDA / 6FCDA-SBI was measured by the constant volume / variable pressure method. In order to remove any contaminants in the permeation system and membrane, the system with a masking membrane in a sealed permeation cell was degassed for 24 hours. The pure gas permeabilities of He, H2, N2, O2, CH4 and CO2 were measured at 2 bar and 35 °C. The gas permeabilities were determined as follows:
[0065] In the formula, the permeability coefficient P is expressed in barrer (1 barrer = 10 -10 cm 3 (STP)⋅cm cm -2 ⋅s -1 ⋅cm Hg -1 or 7.5 × 10 -18 m 3 (STP)⋅mm -2 ⋅s -1 ⋅Pa -1 ) as the unit; p up is the upstream pressure (cm Hg); T is the operating temperature (K); V d is the permeate volume (cm3); dp / dt is the permeate pressure change (cm Hg⋅s -1 ); A is the effective area of the membrane (cm 2 ), l is the thickness (cm), R is the gas constant, which is equal to 0.278 cm 3 cm Hg cm -3 (STP)⋅K -1 . Pure gas selectivity α AB The calculation is as follows:
[0066] Among them, the permeability coefficients of gas A and gas B are denoted as P A , P B , D A , D B , S A , S B are the diffusion coefficients of A and B and the solubility coefficients of A and B, respectively. Each polymer membrane was tested three times, and the deviations of permeability and selectivity were within the range of ~5%. The specific results are as follows: The nitrogen permeability coefficient is 42.62 Barrer, the oxygen permeability coefficient is 165.25 Barrer, the methane permeability coefficient is 40.35 Barrer, the carbon dioxide permeability coefficient is 1082.96 Barrer, and the hydrogen permeability coefficient is 833.40 Barrer; The selectivity coefficient of hydrogen / methane is 20.66, the selectivity coefficient of oxygen / nitrogen is 3.88, and the selectivity coefficient of carbon dioxide / methane is 26.84.
[0067] Example 1-2 A method for preparing an ultrafine PBO hollow fiber gas separation membrane comprises the following steps: (1) The method is the same as step (1) of Example 1-1; (2) The polyimide (6FCDA-HAB) with linked oxygen atoms was dissolved in a benign solvent, N-methylpyrrolidone, and a porogen, polyvinylpyrrolidone, and a low-boiling-point solvent, tetrahydrofuran, were added to prepare a casting solution with a solid content of 25%wt; 100g of polyimide and 243ml of N-methylpyrrolidone (1.028g / cm 3 ), tetrahydrofuran 52ml (0.89g / cm3), polyvinyl pyrrolidone 4g.
[0068] The casting liquid was placed in a material tank for degassing for 24 h, and a mixed solution of NMP: water = 90:10 was selected as the core liquid. The flow rate ratio of the core liquid to the casting liquid was 1:3. Dry-jet wet spinning was carried out at a drawing speed of 15 m / min to obtain a hollow fiber membrane. (3) The method is the same as step (3) of Example 1-1, except that the thermal rearrangement temperature is 440° C. and the thermal rearrangement time is 2 h, thereby obtaining an ultrafine PBO hollow fiber gas separation membrane with an outer diameter of 400 μm.
[0069] Structural characterization: The SEM of the obtained ultrafine PBO hollow fiber gas separation membrane is as follows: Figure 5 (a) shown.
[0070] Gas separation performance test: The method is the same as Example 1-1, and the specific results are as follows: The nitrogen flux is 7.12 GPU, the oxygen flux is 36.4 GPU, the methane flux is 6.68 GPU, the carbon dioxide flux is 235.87 GPU, and the hydrogen flux is 414.65 GPU; The selectivity coefficient of hydrogen / methane is 62.07, the selectivity coefficient of oxygen / nitrogen is 5.11, and the selectivity coefficient of carbon dioxide / methane is 35.31.
[0071] Comparative Example 1-1 A method for preparing a symmetrical film of polybenzoxazole (PBO) based on a non-ladder-structured dianhydride comprises the following steps: The PBO structure in the PBO film (denoted as 6FDA-HAB-TR) is as follows:
[0072] (1) Under argon protection, 2, 2'-bis(3, 4-dicarboxylic acid)hexafluoropropane dianhydride (denoted as: 6FDA) (0.8884 g, 2 mmol), 3,3'-dihydroxybenzidine (denoted as: HAB) (0.4324 g, 2 mmol) and m-cresol (6 mL) were added to a 25 mL polymerization tube in sequence, and 1 mL of isoquinoline was added dropwise. A magnetic bar was added for stirring, and the mixture was heated to 160 °C for 3 h. The product was brown and viscous with a viscosity of about 10w cps. The obtained viscous solution was slowly poured into a stirred ethanol / water = 1:1 mixed solution (1000 mL). The polymer solution precipitated in a fibrous state, stirred, and then filtered to obtain the product. The mixed solvent of ethanol and water was replaced 5 times to completely remove the unreacted m-cresol, and finally dried in a vacuum oven at 120 ° C for 15 h until constant weight was obtained to obtain a polymer, and polyimide GPI was obtained, also recorded as 6FDA-HAB; (2) The obtained PI was dissolved in tetrahydrofuran to prepare a solution with a solid content of 2%wt. The insoluble matter and impurities were removed by a filter. The filtered solution was poured into a petri dish with a diameter of 6 cm, and the solvent was evaporated, and the polymer phase was transformed into a membrane. The solvent was evaporated cleanly to obtain a transparent film with a thickness of ~50 μm, which was dried in a vacuum oven at 100 °C for 12 h, and further heated in a tube furnace at 230 °C for 2 h under N2 atmosphere to ensure that the remaining solvent was completely removed, and a polyimide film was obtained, which was also recorded as 6FDA-HAB film; (3) The 6FDA-HAB film was subjected to thermal rearrangement treatment, specifically: polyimide was placed in a crucible, and the thermal weight loss of polyimide was analyzed by a thermogravimetric analyzer in a nitrogen atmosphere at a heating rate of 5 °C / min from 30 °C to 800 °C. Thermogravimetric analysis showed that it began to rearrange at 400 °C, and the thermal rearrangement reaction rate reached the maximum at 440 °C. The temperature for thermal rearrangement was finally determined to be 450 °C, and the time required for thermal rearrangement was 2 h. After naturally cooling to room temperature, a polybenzoxazole symmetric film GPO was obtained, which was recorded as 6FDA-HAB-TR film.
[0073] Structural characterization: 6FDA-HAB: 1 H NMR (400 MHz, DMSO-d6) δ 9.59 (s, 2H, -OH), 8.15 (d, J =7.9 Hz, 2H), 7.97 (s, 2H), 7.77 (s, 2H), 7.16 (s, 3H), 6.43 (s, 3H). The peaks in the H NMR spectrum of 6FDA-HAB(GPI) are as follows: Figure 1 shown.
[0074] The infrared spectra of the obtained 6FDA-HAB (GPI) and 6FDA-HAB-TR films (GPO) were 1780, 1720, and 1380 cm - The absorption peak of the imide ring is shown at ¹ Figure 2 shown. Gas separation performance test: The method is the same as Example 1-1, and the specific results are as follows: The nitrogen permeability coefficient is 17.76 Barrer, the oxygen permeability coefficient is 70.39 Barrer, the methane permeability coefficient is 16.52 Barrer, the carbon dioxide permeability coefficient is 320.74 Barrer, and the hydrogen permeability coefficient is 280.35 Barrer; The selectivity coefficient of hydrogen / methane is 16.97, the selectivity coefficient of oxygen / nitrogen is 3.96, and the selectivity coefficient of carbon dioxide / methane is 19.42.
[0075] In addition, in order to further analyze and compare the performance advantages of the film prepared by the preparation method of the present invention, the inventors analyzed the micropores of the polymer powder before and after heat treatment by N2 adsorption isotherms at 77 K, as shown in FIG. Figure 3 As shown in a. According to the adsorption curve between p / p0 of 0.04 and 0.32, the BET surface area can be obtained. The surface area of both polymers (GPI, GCPI) increased after heat treatment. The formation of PBO structure promoted the increase of surface area and was also the main reason for the increase of free volume fraction. Compared with GCPI and GPI, the former has a larger surface area, which is inseparable from the connection of oxygen atoms. The connection of oxygen atoms keeps the polymer chain in a ladder structure, limits the stacking of polymer chains, and provides a higher free volume. The pore size distribution (PSD) of GPI, GPO, GCPI and GCPO can be obtained by the Horv ́ath-Kawazoe (HK) method, as shown in Figure 3 As shown in Figure b, GCPO has the largest micropore volume, GPI has the smallest micropore volume, and GCPI has a larger micropore volume than GPO. This is because the connection of oxygen atoms limits the stacking of polymer chains, GCPI has more free volume and cavities, and more micropores are formed on the surface.
[0076] like Figure 4 Shown is a comparison chart of the separation performance of the polyimide and polyimide film obtained in Example 1-1 of the present invention and Comparative Example 1-1.
[0077] GPI has a relatively low flux, with a CO2 permeability of 92.84 Barrer, an O2 permeability of 17.82 Barrer, a CO2 / CH4 selectivity of 35.28, and an O2 / N2 selectivity of 4.98. It is a low-flux, high-selectivity polymer. The CO2 permeability of GCPI is 763.51 Barrer, and the O2 permeability is 128.23 Barrer. Compared with GPI, the CO2 flux of GCPI is more than 7 times higher, and the O2 flux is also more than 7 times higher. The selectivity (α CO2 / CH4 is 25.4, α O2 / N2 The reason for the huge change in flux is that the oxygen atom is linked to the GCPI dianhydride. The oxygen element is linked to the original twisted dianhydride, which restricts the polyimide precursor that can be twisted. The precursor remains in a cavity state supported by oxygen atoms, which improves the stacking efficiency of the polymer chain. The average chain spacing of the polymer chain remains in a stable state, increasing the free volume, so that the flux of GCPI is greatly improved on the original basis, and the selectivity is slightly reduced.
[0078] GPI and GCPI were heat treated to obtain TR polymer membranes GPO and GCPO with PBO structure. Compared with GPI, the gas permeability of GPO (O2 permeability is 70.39 Barrer, CO2 permeability is 320.74 Barrer, O2 / N2 selectivity is 3.96, and CO2 / CH4 selectivity is 19.42) has greatly improved gas permeability and decreased selectivity, mainly because a large amount of free volume enters between the polymer chains during the thermal rearrangement process, forming more micropores on the surface of the membrane, resulting in a significant increase in permeability and a slight decrease in selectivity. The permeability of GCPO (O2 permeability is 165.25 Barrer, CO2 permeability is 1082.96 Barrer, O2 / N2 selectivity is 3.88, and CO2 / CH4 selectivity is 26.84) has increased significantly, but the selectivity has not decreased, which is because the linkage of oxygen atoms enhances the rigidity of the polyimide main chain. Moreover, during the thermal rearrangement process, GCPI completes the thermal rearrangement process earlier than GPI. Under the same reaction conditions, the main chain of GCPI decomposes more and gradually approaches graphitization. More micropores are formed on the surface, and the screening performance for gas molecules is higher. Therefore, the flux of GCPO increases and the selectivity also increases.
[0079] Example 2-1 A method for preparing a symmetrical film of polybenzoxazole (PBO) based on a ladder-structured dianhydride comprises the following steps: The reaction formula of PBO film (6FCDA-APAE-TR) is as follows:
[0080] (1) Under argon protection, 6FCDA (0.9164 g, 2 mmol), HAB (0.7325 g, 2 mmol) and m-cresol (6 mL) were added to a 25 mL polymerization tube in sequence, and 1 mL of isoquinoline was added dropwise. A magnetic bar was added for stirring, and the mixture was heated to 160 °C for 3 h. The product was brown and viscous with a viscosity of about 10w cps. The obtained viscous solution was slowly poured into a stirred ethanol / water = 1:1 mixed solution (1000 mL), and the polymer solution was precipitated in a fibrous state, stirred, and then filtered to obtain the product. The mixed solvent of ethanol and water was replaced 5 times to completely remove the unreacted m-cresol, and finally dried in a vacuum oven at 120 ° C for 15 h until constant weight was obtained to obtain a polymer, and a polyimide was obtained, which was recorded as 6FCDA-APAF. (2) The obtained PI was dissolved in tetrahydrofuran to prepare a solution with a solid content of 2%wt. The insoluble matter and impurities were removed by a filter, and the filtered solution was poured into a petri dish with a diameter of 6 cm. The solvent was evaporated and the polymer phase was transformed into a membrane. After the solvent was evaporated, it was dried in a vacuum oven at 100 °C for 12 h, and further heated in a tube furnace at 230 °C for 2 h under N2 atmosphere to ensure that the remaining solvent was completely removed to obtain a polyimide film, which was recorded as 6FCDA-APAF film.
[0081] (3) The 6FCDA-APAF film was subjected to thermal rearrangement treatment, specifically: polyimide was placed in a crucible, and the thermal weight loss of polyimide was analyzed by a thermogravimetric analyzer in a nitrogen atmosphere at a heating rate of 5 °C / min from 30 °C to 800 °C. Thermogravimetric analysis showed that it began to rearrange at 400 °C, and the thermal rearrangement reaction rate reached the maximum at 450 °C. The temperature at which the thermal rearrangement occurred was finally determined to be 450 °C, and the time required for the thermal rearrangement to occur was 2 h. After naturally cooling to room temperature, a symmetrical polybenzoxazole film was obtained, which was recorded as 6FCDA-APAF-TR film with a thickness of 60 µm. Structural characterization: 6FCDA-APAF: 1 H NMR (400 MHz, DMSO-d6) δ 9. (s, 2H, -OH), 8.27 (s, 2H), 8.08 (s, 2H), 7.18 (s, 3H), 6.51 (s, 3H). Gas separation performance test: The method is the same as Example 1-1, and the specific results are as follows: The gas separation test of the obtained 6FCDA-APAF-TR membrane showed that the nitrogen permeability coefficient was 38.78 Barrer, the oxygen permeability coefficient was 159.67 Barrer, the methane permeability coefficient was 38.57 Barrer, the carbon dioxide permeability coefficient was 987.63 Barrer, and the hydrogen permeability coefficient was 800.54 Barrer; The selectivity coefficient of hydrogen / methane is 20.76, the selectivity coefficient of oxygen / nitrogen is 4.12, and the selectivity coefficient of carbon dioxide / methane is 25.61.
[0082] Example 2-2 The preparation method of the hollow fiber gas separation membrane (6FCDA-APAF-TR) comprises the following steps: (1) Same as step (1) of Example 2-1; (2) The polyimide (6FCDA-APAF) with linked oxygen atoms was dissolved in N-methylpyrrolidone, and a porogen and a volatile solvent were added to prepare a casting solution with a solid content of 25%wt. Polyimide 100 g, N-methylpyrrolidone 243 ml (1.028 g / cm 3 ), tetrahydrofuran 52 ml (0.89 g / cm 3 ), polyvinyl pyrrolidone 4 g.
[0083] The casting solution was placed in a tank for degassing for 24 h, and a mixed solution of NMP: water = 90:10 was selected as the core solution, and the flow rate ratio of the core solution to the casting solution was 1:3. Dry-jet wet spinning was performed at a drafting speed of 15 m / min to prepare a hollow fiber membrane.
[0084] (3) The method is the same as step (3) of Example 2-1, except that the thermal rearrangement temperature is 450°C and the thermal rearrangement time is 3 h, thereby obtaining an ultrafine PBO hollow fiber gas separation membrane with an outer diameter of 380 μm.
[0085] The SEM of the ultrafine PBO hollow fiber gas separation membrane prepared in this example is as follows: Figure 5 (b) shown.
[0086] Gas separation performance test: The method is the same as Example 1-1, and the specific results are as follows: The nitrogen flux is 6.85 GPU, the oxygen flux is 33.54 GPU, the methane flux is 6.21 GPU, the carbon dioxide flux is 224.36 GPU, and the hydrogen flux is 405.62 GPU; The selectivity coefficient of hydrogen / methane is 65.32, the selectivity coefficient of oxygen / nitrogen is 4.90, and the selectivity coefficient of carbon dioxide / methane is 36.13.
[0087] Comparative Example 2-1 A method for preparing a polybenzoxazole (PBO) film based on a non-ladder structure dianhydride comprises the following steps: The reaction formula of thermally rearranged polybenzoxazole symmetric film (6FDA-APAE-TR) in this embodiment is as follows:
[0088] (1) Under argon protection, 6FDA (0.8884 g, 2 mmol), APAF (0.7325 g, 2 mmol) and m-cresol (6 mL) were added to a 25 mL polymerization tube in sequence, and 1 mL of isoquinoline was added dropwise. A magnetic bar was added for stirring, and the mixture was heated to 160 °C for 3 h. The product was brown and viscous with a viscosity of about 10w cps. The obtained viscous solution was slowly poured into a stirred ethanol / water = 1:1 mixed solution (1000 mL). The polymer solution precipitated in a fibrous state, stirred, and then filtered to obtain the product. The mixed solvent of ethanol and water was replaced 5 times to completely remove the unreacted m-cresol, and finally dried in a vacuum oven at 120 ° C until constant weight to obtain a polymer, which was recorded as 6FDA-APAF; (2) The obtained PI was dissolved in tetrahydrofuran to prepare a solution with a solid content of 2%wt. The insoluble matter and impurities were removed by a filter. The filtered solution was poured into a petri dish with a diameter of 6 cm. The solvent was evaporated and the polymer phase was transformed into a membrane. After the solvent was evaporated, it was dried in a vacuum oven at 100 °C for 12 h, and further heated in a tube furnace at 230 °C for 2 h under N2 atmosphere to ensure that the remaining solvent was completely removed to obtain a polyimide film, which was recorded as 6FDA-APAF film; (3) 6FDA-APAF was subjected to thermal rearrangement treatment, specifically: polyimide was placed in a crucible, and the thermal weight loss of polyimide was analyzed by a thermogravimetric analyzer in a nitrogen atmosphere at a heating rate of 5 °C / min from 30 °C to 800 °C. Thermogravimetric analysis showed that it began to rearrange at 400 °C, and the thermal rearrangement reaction rate reached a maximum at 440 °C. The temperature at which thermal rearrangement occurred was finally determined to be 450 °C, and the time required for thermal rearrangement was 2 h. After naturally cooling to room temperature, a symmetrical polybenzoxazole film was obtained, which was recorded as 6FDA-APAF-TR. Structural characterization: 6FDA-HAB: 1 H NMR (400 MHz, DMSO-d6) δ 9. 67 (s, 2H, -OH), 8.23 (d, J =7.9 Hz, 2H), 7.89 (s, 2H), 7.65 (s, 2H), 7.06 (s, 3H), 6.54 (s, 3H). Gas separation performance test: The method is the same as Example 1-1, and the specific results are as follows: The nitrogen permeability coefficient is 16.57 Barrer, the oxygen permeability coefficient is 68.85 Barrer, the methane permeability coefficient is 14.89 Barrer, the carbon dioxide permeability coefficient is 310.65 Barrer, and the hydrogen permeability coefficient is 276.37 Barrer; The selectivity coefficient of hydrogen / methane is 18.56, the selectivity coefficient of oxygen / nitrogen is 4.16, and the selectivity coefficient of carbon dioxide / methane is 20.86.
[0089] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A polybenzoxazole symmetrical film, characterized in that: The polybenzoxazole has a structure as shown in formula (I): Formula (I); Among them, 10 <n<500; X is independently selected from: , , , , , or ; Ar is independently selected from: , , , , , or .
2. The method for preparing a polybenzoxazole symmetrical film according to claim 1, characterized in that: The steps include: S1. Under a protective atmosphere, a ladder-shaped dianhydride and an o-hydroxy diamine are mixed, a catalyst and a solvent are added, and the temperature is raised to 150-180° C. to react to obtain a viscous reaction solution; S2, treating the viscous reaction solution by solvent precipitation method, drying, and obtaining polyimide; S3, dissolving the polyimide in a solvent, placing the resulting solution in a culture dish, and evaporating the solvent to obtain a polyimide film; S4, placing the polyimide film in a tube furnace, and heat treating it at 350-500° C. for 0.5-2 h to obtain a polybenzoxazole symmetrical film; Wherein, in step S1, the ladder-structured dianhydride is selected from the following: ; wherein X is independently selected from: , , , , , or .
3. The preparation method according to claim 2, characterized in that: In step S1, the o-hydroxy diamine is selected from the following: 、 、 、 , , or .
4. The preparation method according to claim 2, characterized in that: In step S1, the ratio of the ladder-structured dianhydride, o-hydroxydiamine, and catalyst is 2 mmol:2 mmol:0.3~2 mL.
5. The preparation method according to claim 2, characterized in that: In step S1, the catalyst is selected from a basic catalyst or an acidic catalyst; Preferably, the alkaline catalyst comprises at least one of isoquinoline and triethylamine; Preferably, the acidic catalyst includes at least one of benzoic acid and p-hydroxybenzoic acid.
6. The preparation method according to claim 2, characterized in that: In step S2, the viscous reaction liquid is treated by a solvent precipitation method, which specifically includes: pouring the viscous reaction liquid into a mixed solution of ethanol and water, stirring to precipitate polyimide, and filtering; wherein the volume ratio of ethanol to water in the mixed solution of ethanol and water is 1:1; In step S2, the drying is specifically performed at 80-120° C. for 10-20 h.
7. The preparation method according to claim 2, characterized in that: In step S1, the solvent includes at least one of m-cresol, N-methylpyrrolidone, N, N-dimethylformamide, N, N-dimethylacetamide, and dimethyl sulfoxide; In step S3, the solvent is a volatile solvent; preferably, the volatile solvent includes at least one of tetrahydrofuran, 1,4-dioxane, chloroform and dichloromethane.
8. An ultrafine polybenzoxazole hollow fiber asymmetric membrane, characterized in that: The polybenzoxazole has a structure as shown in formula (I): Formula (I); Among them, 10 <n<500; X is independently selected from: , , , , , or ; Ar is independently selected from: , , , , , or .
9. The method for preparing the ultrafine polybenzoxazole hollow fiber asymmetric membrane according to claim 8, characterized in that: The steps include: Y1. Dissolve polyimide in a benign solvent, add a porogen and a low boiling point solvent, and stir to obtain a casting solution; Y2, placing the casting solution obtained in step Y1 into a material tank for degassing, and obtaining an ultrafine hollow fiber gas separation membrane by dry-jet wet spinning; Y3, placing the ultrafine hollow fiber gas separation membrane obtained in step Y2 in a tubular furnace at 350-500° C. for heat treatment for 0.5-2 h to obtain an ultrafine PBO hollow fiber gas separation membrane; Wherein, in step Y1, the polyimide is obtained through steps S1-S2 in the method for preparing polybenzoxazole according to claim 3.
10. Use of the polybenzoxazole symmetrical film according to claim 1 and the ultrafine polybenzoxazole hollow fiber asymmetric membrane according to claim 8 in gas separation, characterized in that: The applications include: A polybenzoxazole symmetrical film or an ultrafine polybenzoxazole hollow fiber asymmetric membrane is used to obtain H2 from a H2 / N2 mixed gas, to enrich O2 from an O2 / N2 mixed gas or to obtain high-concentration N2 from the air, to separate CO2 from a CO2 / CH4 mixed gas, to separate H2 from a H2 / CH4 mixed gas or to separate CO2 from a CO2 / N2 mixed gas.